2006
DOI: 10.1128/aem.01412-06
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Emergence and Distribution of Escherichia coli O157 Genotypes in a Beef Feedlot

Abstract: The purpose of this study was to describe the prevalence and longitudinal distribution of Escherichia coli O157 in feedlot cattle and the feedlot environment. Pen floors, water tanks, other cattle in the feedlot, feed, and bird feces were sampled for 2 weeks prior to entry of the study cattle. Twelve pens of study cattle were sampled twice weekly. At each sample time cattle feces, water from tanks in each pen, bunk feed, feed components, bird feces, and houseflies were collected. Bunk feed samples were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 33 publications
5
14
0
Order By: Relevance
“…These results suggest that either the higher concentrate amounts in the transition phase or the length the cattle are the same cohort (109 d) could aid the persistence of closely related strain types shed. Sanderson et al (2006) made similar observations for pathogenic E. coli and reported change in the strain types over time, but at a much faster rate than observed in this study. In that study, it was reported that PFGE types prior to entry into the feedlot were different from the majority of types identified after entry whereby a single strain type, which was first identified 5 d after entry of cattle, predominated among animals and was subsequently identified in all pens.…”
Section: Strain Characterizationsupporting
confidence: 88%
See 1 more Smart Citation
“…These results suggest that either the higher concentrate amounts in the transition phase or the length the cattle are the same cohort (109 d) could aid the persistence of closely related strain types shed. Sanderson et al (2006) made similar observations for pathogenic E. coli and reported change in the strain types over time, but at a much faster rate than observed in this study. In that study, it was reported that PFGE types prior to entry into the feedlot were different from the majority of types identified after entry whereby a single strain type, which was first identified 5 d after entry of cattle, predominated among animals and was subsequently identified in all pens.…”
Section: Strain Characterizationsupporting
confidence: 88%
“…A previous abattoir surveillance beef cattle study examining generic E. coli reported a lower prevalence rate (27%; 33/122 isolates) of E. coli resistant to ]1 antimicrobials (Public Health Agency of Canada 2005). In a more recent study examining antibiotic resistance in dairy cattle, of the total isolates examined (n 0258), Gram-negative enteric bacteria resistant to ampicillin and tetracycline were isolated from feces of 35 and 42% cattle respectively, of 213 lactating cattle examined (Sawant et al 2007).…”
Section: Phenotypic Characterizationmentioning
confidence: 99%
“…This study used a random subset of rectal fecal samples collected from a much larger investigation of E. coli O157:H7 in feedlots A and B (T. P. Stephens, unpublished data). In this study, the overall prevalence of E. coli O157:H7 in fecal grab samples (23.9%) was high but not unlike that reported previously (20). The high numbers of host persisting during the study period likely increased phage prevalence.…”
Section: Discussionmentioning
confidence: 50%
“…Fecal shedding and the spreading of manure on fields are believed to be some of the agents of contamination (24,45). Better knowledge of the bacterial communities in the rumen and those found in fecal matter may provide insights into the mitigation of fecal bacterial contamination.…”
mentioning
confidence: 99%